Concept and Application of Lecture Methods in Introductory Islamic Studies Lectures - Syiraz Rozaky Bimagfiranda; Wasith Achadi; Radino (al-Afkar, Journal For Islamic Studies, 2024)
This research aims to find out the concept and application of the lecture method in introductory Islamic studies courses. This type of research is qualitative, namely in the form of library research where the data sources come from books, articles and several other literature. The study of this issue was carried out using a character approach based on Islamic teachings, namely the Koran and al-Hadith. The results of this research show that the lecture method in introductory Islamic studies courses is the lecturer's way of delivering introductory Islamic studies learning material by direct oral narrative to students in front of the class accompanied by the use of media to achieve predetermined learning competencies and indicators so that students can have an understanding. and apply it in life in accordance with Islamic teachings. Then, to apply the lecture method in introductory Islamic studies courses, there are five things which include conveying learning objectives, adjusting the accuracy of the method, managing students' attention and condition, presenting material, conducting evaluations.